Implementation of the Registered Nurses' Association of Ontario Best Practice Guidelines for delirium-specific recommendations in a digital practice setting at Humber River Health, Canada. - Yoon, Jennifer; Hutchinson, Derek; Ghuman, Amanpreet; Maghera, Gurmit; Edelstein, Beatrise; Soogree, Rachelle; Payumo, Maritess; Mercieca, Grace; Goguen, Shirley; Leblanc, Elizabeth; Plathanathu, Akhil; Sud, Abhimanyu; et al. (International Journal of Nursing Sciences, 2026)
This study aimed to outline and evaluate three key implementation strategies undertaken by Humber River Health (HRH) nursing leadership to support the sustained implementation of the delirium, dementia & depression Best Practice Guideline (BPG). In 2017, HRH embarked on a high-reliability journey, prioritizing consistent quality and safe care delivery by implementing the Registered Nurses' Association of Ontario (RNAO) Best Practice Guidelines (BPGs). Based on the implementation guidelines, the hospital has also adopted three measures: the use of electronic medical records "DocOpt", embedding the content of delirium into staff training, and constructing health risk blocks with hierarchical early warnings, embedded within our Command Center. From 2019 to 2025, a retrospective longitudinal assessment of hospital inpatients was conducted using process indicators, outcome indicators, and patient satisfaction. Process and outcome metrics were evaluated pre- and post-implementation using Statistical Process Control Charts in Microsoft Excel QI Macros, in which Central Lines and Upper and Lower Lines were calculated. Further, segmented regression was conducted to evaluate key time periods during the implementation of the delirium BPG. Due to the implementation of specific recommendations for delirium, the process indicators of delirium in HRH patients improved from 2019 to 2025, and the incidence of delirium in elderly patients per 1,000 patient care days decreased accordingly, by 1.4 times (accounting for 23.3 %); more than 90 % of patients and their families were satisfied with the hospital. According to the segmented regression analysis, it indicates that from the third quarter of 2019 to the third quarter of 2020, and from the first quarter of 2021 to the first quarter of 2022, there was a transitional period, which marked the period when the "DocOpt" system and health risk blocks were applied. Long-term evaluation of process and outcomes data supported HRH to achieve improved patient delirium outcomes. Future research can rely on the regular, dynamic data-monitoring system to provide more empirical evidence for the localization adaptation, consistent implementation, and continuous quality improvement of BPGs.